Deep Learning-Based Machinery Fault Diagnostics - Chen, Hongtian; Zhong, Kai; Ran, Guangtao; Cheng, Chao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book offers a compilation for experts, scholars, and researchers to present the most recent advancements, from theoretical methods to the applications of sophisticated fault diagnosis techniques. The deep learning methods for analyzing and testing complex mechanical systems are of particular interest. Special attention is given to the representation and analysis of system information, operating condition monitoring, the establishment of technical standards, and scientific support of machinery fault diagnosis.